Dyeing of cotton fabric by Caesalpinia sappan aqueous extract at different temperatures and mordants - Kannathasan, K.; Kokila, P. (Current Botany, 2021)
The colour is one of the most important features in textile industry and customers requirements. Synthetic colours are available at affordable prices due to their bulk production. On the other hand, they pose undesirable taste (in case of foods) and harmful effects to ecosystem. The natural colours when used in textiles do not threat the environments and do not cause any skin allergy, toxicity and other hazards to living things as compared to the synthetic counterparts. In the present study, dyeing experiments were conducted with the aqueous extract of bark chips of Caesalpinia sappan at 60, 80 and100° C and using different mordant treatments. The fastness to washing for most of cotton fabrics showed fair grey scale rating. Among the mordants Alum, CuSo4 and Myrobalan used, the natural mordant myrobalan showed poor fastness properties compared to other two mordants. The staining tests showed that most of fabrics exhibited only slight/completely no pilling in majority of the treatments.